Evaluation of fMRI activation in post-stroke patients with movement disorders after repetitive transcranial magnetic stimulation: a scoping review - Cheng, Siman; Xin, Rong; Zhao, Yan; Wang, Pu; Feng, Wuwei; Liu, Peng (Frontiers in Neurology, 2023)
Background Movement disorders are one of the most common stroke residual effects, which cause a heavy burden on their families and society. Repetitive transcranial magnetic stimulation (rTMS) could change reorganization and plasticity in the brain network, which has been suggested as an alternative rehabilitative treatment for enhancing stroke recovery. Functional magnetic resonance imaging (fMRI) have been served as a promising tool to explore neural mechanisms underlying rTMS intervention. Object Our primary goal is to better understand the neuroplastic mechanisms of rTMS in stroke rehabilitation, this paper provides a scoping review of recent studies, which investigate the alteration of brain activity using fMRI after the application of rTMS over the primary motor area (M1) in movement disorders patients after stroke. Method The database PubMed, Embase, Web of Science, WanFang Chinese database, ZhiWang Chinese database from establishment of each database until December 2022 were included. Two researchers independently screened the literature, extracted the data and the most relevant features extracted to a summary table. Two researchers also assessed the methodological quality with the Downs and Black criteria. Results A total of 711 studies were found in the databases, and 9 were finally enrolled. They were of good quality or fair quality. The literature mainly involved thetherapeutic effect and imaging mechanisms of rTMS on improving movement disorders after stroke. In the real rTMS group compared with sham group in all trials, the neuroplastic effect of rTMS can lead to better functional connectivity in the brain network in assisting stroke recovery. Conclusion rTMS allows the excitation and synchronization of neural activity, changes the functional connectivity between brain regions after stroke, promotes the reorganization of brain function, and achieves the motor function recovery. fMRI can observe the influence of rTMS on brain networks and reveal the neuroplasticity mechanism of post-stroke rehabilitation. The biphasic recovery model of the transcallosal suppression model and the compensatory model may be the neurophysiological basis of functional recovery after stroke